The mediating role of mentalization and integrative self-knowledge in the relationship between childhood trauma and fear of intimacy - Riazi, Seyyedeh Sara; Manouchehri, Mehdi (Frontiers in Psychology, 2024)
Introduction Since intimacy is a fundamental human need within social relationships, and recognizing that a fear of intimacy correlates with various negative consequences, it becomes crucial to examine the origins and factors that contribute to addressing this issue. This research aimed to investigate the mediating roles of mentalization and integrative self-knowledge in the link between childhood trauma and the fear of intimacy. Methods Conducted as correlational descriptive research, our study incorporates a total sample of 303 adult women and men participants aged 20 to 50 in Tehran using the convenience sampling method. They completed the Fear of Intimacy Scale (FIS), the Childhood Trauma Questionnaire (CTQ), the Mentalization Scale (MentS), and the Integrative Self-Knowledge Scale (ISK). To analyze the research data at the descriptive level, frequency, percentage, standard deviation, and Pearson’s correlation coefficient were used, while path analysis tested our hypotheses in SPSS version 26 and AMOS version 24. Fit indices were used to check the model’s fit, and the mediation test was performed using the bootstrapping method. The fit indices revealed an excellent fit of the model with the data (χ2 = 1.51, χ2/df = 1.51, p = 0.219; RMSEA = 0.05; SRMR = 0.02; CFI = 0.99; NFI = 0.99; TLI = 0.99). Results Results indicate mentalization fully mediates the childhood trauma-fear of intimacy relationship (β = 0.14, p < 0.01). However, the indirect relationship between childhood trauma and fear of intimacy through integrative self-knowledge was insignificant. The results also showed that the path coefficient from mentalization to fear of intimacy was negative and significant (β = −0.41, p < 0.001), while the path coefficient from integrative self-knowledge to fear of intimacy was not significant (β = −0.02, p > 0.05). Discussion Based on the current findings indicating the complete mediation of mentalization and the insignificance of the mediation of integrative self-knowledge, we can deduce that enhancing the capacity for mentalization holds promise in effectively addressing intimacy-related issues. Overall, the study suggests mentalization effectively predicts the relationship between childhood trauma and fear of intimacy. This, in turn, may mitigate the detrimental effects of challenging childhood experiences on an individual’s ability to engage in intimacy and cultivate emotional closeness.